The prevalence of hepatitis C virus infection in patients with lichen planus: Case- Control Study - Chabbar, Mustafa Ahmad; Suleman, Hamid; Zreik, Youssef (Journal of medical and pharmaceutical sciences, 2022)
Background: Lichen planus (LP) is an idiopathic inflammatory disease of the skin and mucous membranes. It has been reported to be associated with diseases such as hepatitis C virus infection. However, this association vary from one geographic area to another.Objective: The aim of this study is to assess the prevalence of hepatitis C virus infection and liver enzymes abnormalities among patients with lichen planus compared to controls.Materials and Methods: This case- control study included 204 participants (102 with L.P. and 102 controls) from the dermatology clinic at Tishreen University Hospital, Lattakia, Syria, during the period (2020- 2021). The diagnosis was made clinically and confirmed histologically whenever the clinical features were not inclusive. Sera were analyzed for anti- HCV antibodies and liver enzymes; aspartate aminotransferase (AST), alanine aminotransferase (ALT).Results: Out of 102 cases and 102 controls, none was tested positive for Anti- HCV antibodies. There were no statistically significant differences neither in serum levels of liver enzymes; alanine aminotransferase (ALT) (P.value= 0.4), aspartate aminotransferase (AST) (P.value= 0.08) nor in frequencies of its abnormalities; alanine aminotransferase (ALT) (P.value= 0.2), aspartate aminotransferase (AST) (P.value= 0.1) in any of the studied groups.Conclusion: This study did not reveal association between lichen planus and HCV infection, neither revealed any statistically significant elevation in serum levels of liver enzymes among patients with lichen planus compared to controls.
Keywords: Lichen planus; Hepatitis C; Liver enzymes